Urban Energy Scenario: the Case of Kathmandu Valley - Shrestha, Maria E. I.; Sartohadi, Junun; Ridwan, Mohammad Kholid; Hizbaron, Dyah R. (ITB Journal Publisher, LPPM ITB, 2017)
Rapid urbanization has made Kathmandu Valley one of the fastest growing metropolitan cities in South Asia, resulting in the need of additional facilities and infrastructure. The local energy crisis is one of the issues to be addressed. High dependence on imported fossil fuels and the sluggish development of hydropower for electricity generation despite abundant water resources are the major causes to be blamed for the energy crisis in Nepal. This study investigated possible strategies to be implemented in Kathmandu Valley to deal with the discrepancy between energy demand and supply. Several scenarios have been developed and analyzed, both quantitatively and qualitatively. The Comprehensive Scenario, which borrowed from all other developed scenarios, seems superior to the others. It reduces the energy demand by 32.36%, the GHG emission by 44.12%, and the social cost by 33.79%. This scenario implies that the Kathmandu Valley authority will support the installation of photovoltaic solar panels, the use of electric vehicles and electric cookers, and convert solid waste into energy. However, the EV Scenario (electric vehicles) is the one to be given priority in the implementation for its better performance than the other individual scenarios.